The Effect of C-Organic Sediment and Litter Carbon Estimation on Fertility and Site Health in Lampung Mangrove Center - Syahiib, A. Nizam; Safe'i, Rahmat (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Subsurface carbon storage reflects the fertility of mangrove sites. Site fertility has implications for site health. The aims of this study, among others, are to determine the content of C-organic sediments, determine the litter carbon content, and understand the effect of C-organic and litter carbon on on-site health (soil pH and CEC). The stages of research, among others, are sediment and litter sampling on the observation plot, analysis of sediment and litter samples in the laboratory, calculation of litter carbon by dry weight, and fertility analysis of site health using multiple linear regression analysis with a significant threshold of 95%. Based on the results of the study, the highest C-organic content was observed in cluster plot 3 (CL3); the highest increase in litter carbon was at CL2, and there was a significant effect between site fertility (C-organic) and site health (pH). The pH and carbon play a role in the mobility of compounds that form organic materials. Factors influencing on-site carbon health conditions include waste production, organic material, temperature, tree species, pollution, and climate. Sediment conditions affect sigh in organic matter and the health of the site. The results of this research can illustrate the fertility and health conditions of sites in mangrove forests, so regulations can be formulated to prevent damage to mangroves.